2015
DOI: 10.5267/j.uscm.2015.6.001
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain management under the effect of trade credit for deteriorating items with ramp-type demand and partial backordering under inflationary environment

Abstract: In this paper, a supply chain inventory model is developed in inflationary environment by incorporating some realistic features such as ramp type demand, deterioration, partial backlogging, inflation, and trade credit. Here, rate of deterioration is linear and partial backlogging rate is variable and dependent on the waiting time for the next replenishment. Depending on the trade credit period, three different situations arise. For each model the optimal replenishment policy is determined. Numerical examples a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
4
0
2
Order By: Relevance
“…La Industria 4.0 trae cambios disruptivos a las cadenas de suministro, modelos de negocios y procesos de negocios (Figura 10). Los principios de Industria 4.0 son interoperabilidad, virtualización, descentralización, capacidad en tiempo real, orientación de servicio y modularidad (Shastri, Singh, y Gupta, 2015). La Industria 4.0 se puede resumir como un proceso de fabricación integrado, adaptado, optimizado, orientado al servicio e interoperable, que se correlaciona con algoritmos, big data y altas tecnologías.…”
Section: Marco Conceptualunclassified
“…La Industria 4.0 trae cambios disruptivos a las cadenas de suministro, modelos de negocios y procesos de negocios (Figura 10). Los principios de Industria 4.0 son interoperabilidad, virtualización, descentralización, capacidad en tiempo real, orientación de servicio y modularidad (Shastri, Singh, y Gupta, 2015). La Industria 4.0 se puede resumir como un proceso de fabricación integrado, adaptado, optimizado, orientado al servicio e interoperable, que se correlaciona con algoritmos, big data y altas tecnologías.…”
Section: Marco Conceptualunclassified
“…Guchhait et al [16] developed inventory policy of a deteriorating item with variable demand under trade credit period. Shastri et al [33] developed a supply chain inventory model in inflationary environment by incorporating some realistic features such as ramp type demand, deterioration, partial backlogging, inflation and trade credit.…”
Section: Introductionmentioning
confidence: 99%
“…developed a production model for integrated inventory with preservation technology and trade credit period. Shastri et al (2015) suggested a supply chain management with ramp-type demand and partial backordering under trade credit effect.…”
Section: Introductionmentioning
confidence: 99%